2013
DOI: 10.1371/journal.pone.0074592
|View full text |Cite
|
Sign up to set email alerts
|

A Recombinant Anticarsia gemmatalis MNPV Harboring chiA and v-cath Genes from Choristoneura fumiferana Defective NPV Induce Host Liquefaction and Increased Insecticidal Activity

Abstract: One of the interesting features of Anticarsia gemmatalis multiple nucleopolyhedrovirus isolate 2D (AgMNPV-2D) genome is the absence of chitinase (chiA) and cathepsin (v-cath) genes. This characteristic may be responsible for the lack of liquefaction and melanization in A. gemmatalis larvae killed by AgMNPV-2D infection. This study aimed to test the hypothesis that CHIA and V-CATH proteins from Choristonera fumiferana DEF multiple nucleopolyhedrovirus (CfDEFNPV) are able to liquefy and melanize the cuticle of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 49 publications
0
9
0
6
Order By: Relevance
“…invirae, no viruses have been isolated from this insect (Lemos et al, 2009a(Lemos et al, , 2009bLima et al, 2013;Ribeiro et al, 2010;Tinôco, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…invirae, no viruses have been isolated from this insect (Lemos et al, 2009a(Lemos et al, , 2009bLima et al, 2013;Ribeiro et al, 2010;Tinôco, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, cathepsin is synthesized as a proenzyme and later cleaved to produce the mature form, which seems to be assisted by chitinase (Hom et al, 2002). The introduction of chitinase and cathepsin genes into the AgMNPV genome induced host liquefaction and increased insecticidal activity (Lima et al, 2013). In this study, chitinase and cathepsin were identified as components of the ClanGV ODV particle.…”
Section: Newly Identified Odv Proteinsmentioning
confidence: 72%
“…Notably, Anticarsia gemmatalis MNPV (AgMNPV), an alphabaculovirus closely related to AcMNPV, lacks both chitinase and cathepsin (Table). As expected, AgMNPV-infected Anticarsia gemmatalis caterpillars remain intact after death; however, if AgMNPV is engineered to express the chitinase and cathepsin genes from the baculovirus Choristeneura fumirerana MNPV (CfMNPV), liquefaction occurs (Lima et al, 2013). Carefully choreographed chitinase and cathepsin expression and activity during virus replication are crucial for the collaborative work of these enzymes.…”
Section: Baculovirus-encoded Degradative Enzymesmentioning
confidence: 73%